2021
DOI: 10.3389/fcvm.2021.763851
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Dihydrofolate Reductase Gene Knock-In Zebrafish Strain to Aid Preliminary Analysis of Congenital Heart Disease Mechanisms

Abstract: Background: The dihydrofolate reductase (DHFR) gene is imperative in development, therefore it is essential to explore its effects on heart development. Thus, here a dhfr zebrafish knock-in (KI) strain was constructed.Methods: CRISPR/Cas9 technology was used to establish the dhfr KI zebrafish strain. This strain was hybridized with TgG fluorescent strain zebrafish to observe the phenotypes of heart shape, size, and circularization direction. Wild-type (WT) and KI zebrafish were then dissected and histologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The DNA methylation status of the upstream region is critical because of its role in regulating gene expression [ 20 ]. Two genes with abnormal CCGG methylation in the upstream region, Smad3 [ 21 ] and Dhfr [ 22 ], were selected from the results of Methylation-RAD sequencing because of their previously established roles in CHD. qRT-PCR showed that the expression of smad3 mRNA was decreased ( Fig 5A ) and the expression of dhfr mRNA was increased in the diabetic group ( Fig 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…The DNA methylation status of the upstream region is critical because of its role in regulating gene expression [ 20 ]. Two genes with abnormal CCGG methylation in the upstream region, Smad3 [ 21 ] and Dhfr [ 22 ], were selected from the results of Methylation-RAD sequencing because of their previously established roles in CHD. qRT-PCR showed that the expression of smad3 mRNA was decreased ( Fig 5A ) and the expression of dhfr mRNA was increased in the diabetic group ( Fig 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Both Cas9 protein and mRNA have successfully been used in the past to generate zebrafish KI lines 14 , 24 , 27 , 28 . Despite similar somatic editing efficiencies, higher rates of germline transmission have been observed for protein compared to mRNA 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to modeling is to simulate the symptoms of the target disease through mutations in genes with known function. Individuals and lines have been created that exhibit analogs of human somatic diseases such as cataract [ 49 , 50 ], myopia [ 51 ], exfoliative syndrome [ 52 ], retinal dysfunction [ 53 , 54 ], congenital heart defect [ 55 ], cardiac hypertrophy [ 56 ], dilated cardiomyopathy [ 57 ], arrhythmia [ 58 ], autoinflammatory syndrome [ 59 ], metabolic syndrome [ 60 ], diabetes and obesity [ 61 ], tuberculosis [ 62 ], thrombocytopenia [ 63 ], pediatric intestinal pseudoobstruction [ 64 ], pediatric cirrhosis [ 65 ], congenital hypothyroidism [ 66 ], fatty or alcoholic hepatosis [ 67 ], and scoliosis [ 68 , 69 ]. Genome editing has been used to model human tumors such as liver cancer [ 70 ], paraganglioma [ 71 ], skin melanoma [ 72 ], and epithelioid sarcoma [ 73 ].…”
Section: Genome Editing In Salmonidae and Cyprinidae Aquaculture Fish...mentioning
confidence: 99%